Cyber Culture in the Transformation of Urban Da'wah: A Case Study of Pemuda Hijrah Community Bandung, Indonesia - Rustandi, Ridwan; Aliyudin, Mukhlis (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This research aims to analyze the da'wah model carried out among industrial communities. Sociologically, industrial society is characterized by various aspects of heterogeneity in life. As a transition from a phase of social life, industrial society is filled with individual characteristics of society and in multicultural, educational, economic, political, and religious groups. In subsequent developments, the transition to industrial society occurred due to the contribution of technological sophistication, especially information and communication technology. Specifically, research is directed at analyzing the development of cyberculture and its relationship to the transformation of preaching discourse in urban areas. The Pemuda Hijrah Community is the subject and object of the research being observed. The research was conducted from March to June 2024, using an interpretive paradigm, a qualitative approach, and case study methods. Data was collected using observation, documentation, and literature study techniques. The research results show that Hanan Attaki and the Pemuda Hijrah Community in Bandung City can be seen as a case of da'wah activities in industrial society. The characteristics and models of da'wah carried out by Hanan Attaki and Pemuda Hijrah can be a model for developing da'wah activities in urban areas. Therefore, this research found several essential aspects that can be used as a reference in observing the sociological process of da'wah activities in urban areas, which initially only involved young people but influenced various groups development. The impact was not only in Bandung but also became a trendsetter for urban da'wah in multiple regions (villages or cities) in Indonesia.